Macrophage-specific targeting of isoniazid through mannosylated gelatin microspheres - Tiwari S.; Chaturvedi A.P.; Tripathi Y.B.; Mishra B. (My University, 2025)
Active targeting of drug molecules can be achieved by effective attachment of suitable ligands to the surface of carriers. The present work was attempted to prepare mannosylated gelatin microspheres (m-GMs) so as to achieve targeted delivery of isoniazid (INH) to alveolar macrophages (AMs) and maintain its therapeutic concentration for prolonged period of time. Microspheres were prepared by emulsification solvent extraction method and evaluated for physicochemical characteristics, drug release, ex vivo drug uptake by AMs and pharmacokinetic characteristics. Fourier transform infrared spectroscopy and nuclear magnetic resonance spectral analysis confirmed that mannosylation took place through Schiff base formation between aldehyde and amino groups of mannose and gelatin, respectively. Prepared microspheres offered suitable physicochemical characteristics for their delivery to AMs. Their average size was about 4 μm and drug entrapment efficiency of 56% was achieved with them. Ex vivo uptake results indicated that in comparison to plain microspheres, m-GMs were selectively uptaken and were found to be associated with phago-lysosomal vesicles of AMs. Pharmacokinetic studies showed the formulation could maintain the therapeutic concentration of INH for prolonged period of time even with a reduced clinical dose. m-GMs were found to be stable in broncheo-alveolar lavage fluid. The study concluded that ligand decorated carriers could be a potential strategy to improve the therapeutic properties of INH. © 2011 American Association of Pharmaceutical Scientists.